2014
DOI: 10.3844/ajnsp.2014.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rheological Properties of MR Fluid Based on Variation in Concentration of Iron Particles

Abstract: The main aim of this study is to synthesize magneto-rheological fluid in laboratory using silicon oil as carrier oil and it is mixed with variation in concentration of iron particles of size around 4-9 µm, fine lithium grease is used as surfactant. Prepared MR fluid is tested under plate and cone type rheometer for finding is rheological properties like shear stress, shear rate, shear viscosity, storage modulus and loss modulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The shear action on the work-part surface with MRP fluid helps to clip off the roughness crests in the form of micro-chips. 18,19 To understand the material removal mechanism, the in-depth study of the forces imposed on the active abrasives is studied. The iron particles organized themselves in the chains due to the influence of the magnetic field.…”
Section: Rotary Rectangular Tool Core-based Magnetorheological Finishmentioning
confidence: 99%
“…The shear action on the work-part surface with MRP fluid helps to clip off the roughness crests in the form of micro-chips. 18,19 To understand the material removal mechanism, the in-depth study of the forces imposed on the active abrasives is studied. The iron particles organized themselves in the chains due to the influence of the magnetic field.…”
Section: Rotary Rectangular Tool Core-based Magnetorheological Finishmentioning
confidence: 99%
“…Shah et al [37] reported that large particles provide 15 times higher yield stress than small-sized particles. Furthermore, it has been reported that on mixing smaller and larger particles with different weight fractions, the Bingham yield stress value increases by a factor of three compared with large-sized particles dispersed in fluid [38,39]. The finding implies the mechanical properties of MR fluids are the function of temperature; the steps involved in bringing down the off-state viscosity and shear stress at elevated temperatures were studied, as was the performance degradation for a low-high-low temperature cycle [40].…”
Section: Synthesis Of Mr Fluidsmentioning
confidence: 99%
“…A major advantage of a coating of polycyclophenazene is that it would help to reduce the tendency of the magnetic nanoparticles to aggregate together. The potential of such nanoparticles is an active area of research (Zhang et al, 2015;Kamble and Kolckar, 2014). …”
Section: In Vivo Applicationsmentioning
confidence: 99%